Investigation of the 1-week effect of traffic light nutrition labeling on diet selection among Japanese university students: a randomized controlled trial - Nobuyuki Wakui; Raini Matsuoka; Kotoha Ichikawa; Chikako Togawa; Aika Okami; Shoko Kawakubo; Hinako Kagi; Mai Watanabe; Yuika Tsubota; Miho Yamamura; Yoshiaki Machida (BMC, 2024)
Abstract Background The method of displaying nutrition information labels on the front of food packaging (FOP: Front of Pack) has been implemented worldwide to prevent lifestyle-related diseases. This study aimed to investigate whether the use of the UK's Traffic Light Food (TLF) label, known as the FOP label, influences the dietary choices of Japanese youth and promotes healthy dietary choices. Methods Diet selection was performed for one week each during the baseline and intervention periods. During the intervention period, TLF labels were displayed on meal images of the intervention group. Participants chose what they would like to have for dinner of the day from 15 images. Each meal was scored based on the color of the nutrition label, and a comparison between groups was made to determine whether TLF labeling influenced meal selection for dinner. The psychological stress caused by the presence or absence of nutrition labels and nutritional components when choosing meals was also evaluated. Results A total of 69 participants were randomly assigned to two groups. Dietary choice scores indicated that the TLF-labeled group made significantly healthier dietary choices than the unlabeled group. Additionally, the TLF-labeled group showed a significant increase in the percentage of people conscious of nutritional components when choosing meals. Furthermore, a significant increase in the number of people conscious of protein, a nutritional ingredient not indicated on the TLF label, was observed. During the test period, no difference in psychological stress caused by the presence and absence of the TLF labels was observed. Conclusions The use of TLF labels also encouraged healthy dietary choices among Japanese university students. The use of FOP nutrition labels should be considered in Japan to prevent lifestyle-related diseases through healthy dietary choices. Trial registration UMIN Clinical Trials Registry Number: UMIN000047268. Registered March 23, 2022.